Effects of supplementation of nursery diets with an essential fatty acid on immunity in artificially reared pigs - D S McVey; G S Elliot; G A Kennedy; M M Chengappa; N V Anderson; D A Schoneweis; M M Hervey; S M Cowan; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1991)
Twenty four pigs were weaned immediately at farrowing, reared artificially for 21 d, and then used in a 35-d nursery experiment to determine the effects of essential fatty acid deficiency on immune function. Treatments were: 1) a semi-purified diet deficient in essential fatty acids and 2) diet 1 with 2% added linoleic acid. Conversion of linoleic acid to linolenic and then arachidonic acid is a normal step in fatty acid metabolism. Metabolites of arachidonic acid are thought to have a role in mediating immune function. On d 28 of the experiment, pigs were orally dosed with Salmonella choleraesuis to challenge their immune systems. At d 35, pigs fed linoleic acid had greater concentrations of several fatty acids in both small intestine and liver tissues. Also, several measures of arachidonic acid metabolites in the plasma, which activate inflammatory reactions and stimulate white blood cell activity, were greater for pigs fed diets with added linoleic acid. However, no gross lesions were noted at necropsy that would result from infection with S. choleraesuis. Thus, for the short period of this experiment (35 d), deficiency of essential fatty acids apparently had minimal effect on ability of nursery pigs to resist disease.; Swine Day, Manhattan, KS, November 21. 1991
Keywords: Swine day; 1991; Kansas Agricultural Experiment Station contribution; no. 92-193-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 641; Swine; Starter; Essential fatty acid; Immunity; Salmonella choleraesuis